An Unexplored Side of Regeneration Niche: Seed Quantity and Quality Are Determined by the Effect of Temperature on Pollen Performance - Rosbakh, Sergey; Pacini, Ettore; Nepi, Massimo; Poschlod, Peter (Frontiers in Plant Science, 2018)
In 1977, Peter Grubb introduced the regeneration niche concept, which assumes that a plant species cannot persist if the environmental conditions are only suitable for adult plant growth and survival, but not for seed production, dispersal, germination and seedling establishment. During the last decade, this concept has received considerable research attention as it helps to better understand community assembly, population dynamics, and plant responses to environmental changes. Yet, in its present form, it focuses too much on the post-fertilization stages of plant sexual reproduction, neglecting the fact that the environment can operate as a constraint at many points in the chain of processes necessary for successful regeneration. In this review, we draw the attention of the plant ecology research community to the pre-fertilization stages of plant sexual reproduction, an almost ignored but important aspect of the regeneration niche, and their potential consequences for successful seed production. Particularly, we focus on how temperature effects pollen performance and determines plant reproduction success by playing an important role in the temporal and spatial variations in seed quality and quantity. We also review the pollen adaptations to temperature stresses at different levels of plant organization and discuss the plasticity of the performance of pollen under changing temperature conditions. The reviewed literature demonstrates that pre-fertilization stages of seed production, particularly the extreme sensitivity of male gametophyte performance to temperature, are the key determinants of a species’ regeneration niche. Thus, we suggest that previous views stating that the regeneration niche begins with the production of seeds should be modified to include the preceding stages. Lastly, we identify several gaps in pollen-related studies revealing a framework of opportunities for future research, particularly how these findings could be used in the field of plant biology and ecology.